Intriguing Catalytic Activity of Surface Active Gold‐Platinum Islands on Nano‐Porous Au in Determining Efficient Direct Formic Acid Oxidation Pathway. Issue 12 (27th April 2017) - Ganesh, P. Anandha; Jeyakumar, D.
Abstract: Gold‐platinum nano‐porous structures (Au100‐x Ptx NPoS) with unique surface enriched Au−Pt islands are synthesised through a galvanic replacement strategy from Au100‐x Ag2x nano‐alloys with ultra‐low platinum loading (x=1.25, 2.5 and 5). Formic acid oxidation reaction (FAOR) on Au100‐x Ptx /C NPoS shows a distinct peak at around 0.5 V related to CO2 formation. A characteristic peak at around 1.5 V increases with increasing FA concentration owing to the direct FAOR by nano‐porous Au centers. FAOR peaks and If /Ib peak current ratios indicates that, Au100‐x Ptx /C NPoS facilitates direct FAOR pathway unlike HiSPEC Pt/C (dehydration pathway). Based on the enhanced chrono‐amperometric response, Tafel behaviour and mass activity values, Au97.5 Pt2.5 /C NPoS (5.5 A/mgPt ) reflects as the optimal catalyst for efficient FAOR. The intriguing catalytic role of surface enriched Au−Pt islands present on nano‐porous Au greatly helps in determining the superior FAOR activity in Au97.5 Pt2.5 /C NPoS towards direct dehydrogenation pathway at ultra‐low Pt content compared to other NPoS and HiSPEC Pt/C catalysts. Abstract : Predominant dehydrogenation pathway: Au−Pt nano‐porous catalyst exhibits efficient formic acid oxidation through direct dehydrogenation pathway at ultra –low Pt loading attributed to the catalytic role of unique surface Au−Pt islands on nano‐porous Au centres.